MAC protocol to reduce packet collision in wireless sensor network - Halim, AHA; Zen, K (IEEE, 2024)
Wireless sensor network (WSN) consists of a large number of sensor nodes densely deployed closed to each other. Each sensor carries out task such as monitoring and collecting data, or detecting and identifying certain events. nile nodes in operation, they will detect each other and form a communication network. The problem arises when two or more nodes send data at the same times over the same channel. Here, the task of Medium Access Control (MAC) is crucial to efficiently manage the transmission among nodes and reduce collision. However, most of the MAC protocols designed for WSN are for static environment. Applying the existing AMC protocol to application such as medical care and disaster response will raise few problems where the moving node will experience delay in sending and receiving data. Thus, there is a need to design a protocol which can tolerate the node moving without degrading network performance. The aim of this paper is to evaluate the capability of MAC protocol issues especially for the popular MAC protocol for sensor network, S-MAC and IEEE 802.15.4.